Prospectiva de los perfiles ocupacionales de las empresas culturales creativas en el sector radial de la ciudad de Neiva-Huila (2022)
The elaboration of this thesis has the purpose of knowing relevant aspects that can contribute to the strengthening of occupational profiles, providing necessary tools to support processes of creation of cultural creative products and services in an articulated way for the support of production and consumption of the different classes of people integrated for the listener consumption of the different stations, always taking into account the com panies selected within the investigation of the radio sector of the city of Neiva. In the collection of information in which it was carried out, it is done from two sources of information, in the first Source, it is based on interviews with people belongin g to the different stations, dedicated to the creative and cultural industries in companies in the radio sector. of the city of NeivaHuila, in the same way, in the second source, it is based on investigations and documents elaborated by others and that ap proach in the same circumstances and experience of times of the radio sector, contributing important information for our investigation, taking into account It has sectoral studies, dynamic tools that can provide valuable elements to meet the objectives set.